Optimization of temperature distribution in the novel power-to-heat matrix-in-batch OnePot© reactor - Caravella, Alessio; Francardi, Marco; Romano, Salvatore; Prenesti, Giuseppe; Oliverio, Manuela (Frontiers in Energy Research, 2022)
In this work, we assess the optimal temperature distribution inside a new automated, stand-alone, matrix-in-batch patented reactor, named OnePot©. This novel reactor is equipped with seven rotating hot rotating cylinders—here referred to as spots—which make it possible a precise tuning of fluid temperature. To conduct this investigation, we consider two radial layout of spots, here indicated as uniform configuration and alternate one, respectively. The former characterised by a single uniform equilateral triangular pitch, whereas the latter by two different equilateral triangular pitches alternated to form a double-triangle star. We consider two different fluids, water and argon, as representative of the behaviour of liquids and gases, respectively. Furthermore, the effect of viscosity is also taken into account by forcefully increasing that of water by 100 and 1,000 times. The optimization of the temperature distribution is performed obtaining velocity and temperature fields using a computational fluid dynamic (CFD) approach. As a sort of objective function to maximise, we defined a thermal mixing efficiency to provide a quantitative measure of the temperature distribution uniformity. As a remarkable result, we find an optimal value of pitch approximately equal to 36% of the vessel diameter for both liquid water and argon gas. As for the alternate configuration, we found that it provides a better temperature distribution than the uniform one, especially at high viscosity values. This is because the inner spots are able to prevent the formation of large colder “islands” around the centre. Furthermore, we estimate the overall heat transfer coefficient between thermal spots and fluid bulk, whose values are perfectly in line with the literature ones. The modularity of our novel fully-electric reactor allows for applications in a number of industrial contexts, especially pharmaceutical ones.